Systematic Review of Mobile Operating Systems (International Journal of Engineering and Computer Science, 2016)
A mobile operating system (mobile OS) is a system software that allows smartphones and other handheld devices to run applications as well as manage the device’s precious resources like processing power, battery and memory. A mobile OS typically starts up when a device powers on, presenting a screen with icons or tiles with information and through which applications can be accessed. Apart from user applications, mobile operating systems also manage network connectivity. Android, Apple iOS and Blackberry OS are some of the famous mobile operating systems which provides the combined features of personal computer operating systems and the features including touch screen, cellular, Bluetooth, Wi-Fi, GPS navigation system, camera, speech recognition, voice recorder, music player etc. This paper systematically reviews the different operating systems used in the mobile devices